Cytotoxic eremophilane sesquiterpenoids from the saprobic fungus Berkleasmium nigroapicale BCC 8220 - Masahiko Isaka (2018)
Berkleasmins A-E, five new eremophilane sesquiterpenoids were isolated from the saprobic fungus Berkleasmium nigroapicale BCC 8220. The structures of the new compounds were elucidated by analyses of NMR spectroscopic and mass spectrometry data in combination with chemical means. Berkleasmins A and C exhibited cytotoxic activity against cancer cell-lines (NCI-H187, MCF-7, and KB) as well as nonmalignant Vero cells with IC50values of 1.1-7.5 μg/mL, and these compounds also showed antimalarial activity with respective IC50of 3.1 and 2.8 μg/mL. © 2009 Elsevier Ltd. All rights reserved.